- #1

- 1

- 0

Here is my problem:

Prove or disprove: If gcd(m, n) = d, then the gcd(a, mn) = gcd(a,m) * gcd(a.n)/d.

I can seem to get it started, sort of, but it just does not seem to get anywhere. I know by definition d | m and d | n. Then arbitrary integers x and y can be used such that m = xd and n = yd. I can then have gcd(a, mn) = E. Then E | a and E | mn. I can do the same as I did for the other. But the last part of gcd(a,m) * gcd(a.n)/d is giving me a really rough time getting it to know how tie it all in. I have a lot of integers and letters and I think I am very lost at this point. Please help!

melmath

Prove or disprove: If gcd(m, n) = d, then the gcd(a, mn) = gcd(a,m) * gcd(a.n)/d.

I can seem to get it started, sort of, but it just does not seem to get anywhere. I know by definition d | m and d | n. Then arbitrary integers x and y can be used such that m = xd and n = yd. I can then have gcd(a, mn) = E. Then E | a and E | mn. I can do the same as I did for the other. But the last part of gcd(a,m) * gcd(a.n)/d is giving me a really rough time getting it to know how tie it all in. I have a lot of integers and letters and I think I am very lost at this point. Please help!

melmath

Last edited: